Evaluating lead leaching from uPVC pipes into drinking water: Characterization with SEM-EDX and ICP-OES - Yassin T.H. Mehdar (Results in Chemistry)
Unplasticized polyvinyl chloride (uPVC), has become a popular choice for piping systems due to its numerous advantages. Its prevalence in the piping industry is a testament to its versatility, durability, and cost-effectiveness. These uPVC pipes are generally considered safe for use in many applications, there are some health concerns associated with them. One of the main components of uPVC is lead (Pb), which is used as a stabilizer in the manufacturing process. Lead can be leached from these pipes into drinking water, influenced by many factors such as temperature and time. Furthermore, there are many studies about lead exposure and its damage to the kidneys and reproductive system, as well as contributing to elevated blood pressure and hypertension.This study investigates the presence of lead and its leaching rate from some uPVC pipes into drinking water under different conditions of temperature and time. Inductively coupled plasma −optical emission spectrometry (ICP-OES) was used to determine the concentration of Pb in water. In addition, elemental mapping obtained using scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) was utilized to determine the weight percentages of Lead (Pb) on the inner surfaces of the uPVC pipes.The novelty of this study lies in several key aspects that distinguish it from existing literature. It utilizes locally sourced uPVC pipes, which have different manufacturing processes, raw materials, and stabilizers compared to those investigated in previous research. This regional specificity offers new insights that are directly relevant to local public health and regulatory standards. The use of local pipes fills a significant gap in current literature, reflecting regional variations in manufacturing practices.In addition, this study employs a dual-method approach, combining ICP-OES for accurate quantification of lead concentration in water with SEM-EDX for detailed elemental mapping. EDX provides valuable insights into the spatial distribution of lead on pipe surfaces, complementing the quantitative data from ICP-OES. This dual methodology enhances the robustness and comprehensiveness of our findings, offering a more holistic understanding of lead leaching dynamics.